ANALYSIS OF COOPERATIVE PERFORMANCE MEASUREMENT USING THE BALANCED SCORECARD APPROACH (Case Study at KSP Kopdit Harmoni Jaya, Kupang City - Cahyani, Ade Putra Juni; A. Dethan, Minarni; Demu, Yohanes (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
This study examines the application of the Balanced Scorecard method at Kopdit Harmoni Jaya Cooperative in Kupang City. The objective of the research is to measure and evaluate the performance of KSP Kopdit Harmoni Jaya during the period 2022–2024 using the Balanced Scorecard approach. The data were obtained from the Annual Members' Meeting (RAT) reports for 2022–2024 and further confirmed through interviews. This research employs a mixed-methods approach with a case study strategy. The findings indicate that the cooperative's performance in the financial perspective during 2022–2024 scored relatively low based on the assessment indicators specified in the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 06/Per/Dep.6/IV/2016, whereas the non-financial perspectives, including member satisfaction, operational efficiency, and human resource development, showed positive results. Furthermore, this study produces a strategic map that is expected to serve as a reference for the cooperative's future strategic development.